El análisis de los factores que impactan el desempeño laboral del personal administrativo y docente en la Escuela Normal Superior de Michoacán - Navarro Ferreyra, Asís (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The following research constitutes a study of the elements involved in labor performance of staff and faculty at the Escuela Normal Superior de Michoacán (Teacher-Training College of Michoacán). The aim of this research is to provide an account of the extent to which labor performance of personnel is affected by variables such as motivation, economic remuneration and incentives, organizational climate, work environment, work satisfaction and evaluation of personnel. The research methodology’s design is descriptive-correlational, causal, hypothetical, deductive-inductive, and quantitative-qualitative in nature. The sample includes 44 subjects (both staff and faculty personnel). In order to reach the intended aim, I applied a survey of 34 items with descriptive data regarding the variables involved in the study, which is reliable enough for such study. In order to analyze the relevant independent variables, I employed data from the theoretical framework and from the institution, given that the personnel are acquainted with the relevant concepts. The labor performance’s dependent variable clearly shows the average result of the personnel’s assessment of each of the analyzed independent variables. The highest extent of correlation between variables was found in the motivation and work environment correlation, with a value of 0.642; whereas the least correlated variables are organizational climate and labor satisfaction. These results are reasonable given the hypothesis that a substantial amount of personnel motivation follows from work gratification, whereas the rest of the relevant variables are less related to each other given their own nature.

En la presente investigación se estudian los factores del desempeño laboral del personal administrativo y docente de la Escuela Normal Superior de Michoacán. El objetivo trazado en la investigación fue en qué medida las variables: motivación, la remuneración económica incentivos, el clima organizacional, el ambiente laboral, la satisfacción laboral y la evaluación impactan el Desempeño Laboral. La metodología de investigación utilizada, tiene un diseño descriptivo - correlacional, causal, hipotético, deductivo-inductivo y también de carácter cuantitativo – cualitativo. La muestra es de 44 sujetos (personal administrativo y docente). Para lograr el objetivo se aplicó un instrumento con 34 preguntas o ítems con datos descriptivos sobre las variables de estudio. La fiabilidad es adecuada para el estudio. Para el análisis de las variables independientes se utilizaron datos del marco teórico y de la Institución, siendo que el personal administrativo y docente conocen los conceptos. La variable dependiente del Desempeño Laboral muestra claramente el resultado promedio de la valoración que le asignaron a cada una de las variables independientes sujetas a análisis. Las correlaciones entre las variables de motivación y ambiente laboral son las más correlacionadas con un valor de 0.642, mientras las menos correlacionadas son el Clima Organizacional y la Satisfacción Laboral. Siendo que estos resultados parecen muy razonables, porque la persona motivada es porque se siente bien con su trabajo, mientras que las otras variables son aspectos menos relacionados por su propia naturaliza.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2014-1083; Motivación; Remuneración; Incentivos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6035